Alan Splet: o sound design de veludo azul e a polifonia de efeitos sonoros - SOUZA, Fabiano Pereira de (2016)
The work of sound designer Alan Splet (1939-1994) and the importance of the sound effect editing studied through the analysis of the film Blue velvet (USA, 1986), directed by David Lynch. The project aim is to research what characterized Splet’s work with sound effects, if it represented innovation in film language and, if so, how it compared to previous films that had also presented sound effect superposition. Another goal is to verify the applicability of the concepts of polyphony and counterpoint to the sound construction of the film.